2014
DOI: 10.3892/ijmm.2014.1732
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Her-2 upregulates FoxM1 in gastric cancer

Abstract: Abstract. The transcription factor, forkhead box protein M1 (FoxM1), and the tyrosine kinase receptor, human epidermal growth factor receptor-2 (Her-2), are aberrantly expressed in a number of human malignancies, and are closely associated with the development of cancer. However, their regulatory mechanisms and their involvement in tumor development have not been extensively investigated, particularly in gastric cancer. In the present study, we examined the expression levels of FoxM1 and Her-2 in samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Moreover, we found that the Hh-Gli1 signaling pathway regulated the expression of FoxM1 in CRC cells and that the inhibition of FoxM1 impeded Gli1-mediated CRC cell proliferation. FoxM1 expression was also recently reported to be modulated by many other transcription factors, and Her2 reportedly upregulated FoxM1 expression in gastric cancer [ 51 ]. FoxM1 was also shown to be transactivated by HSF1, which promoted the survival of glioma cells under heat shock stress [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that the Hh-Gli1 signaling pathway regulated the expression of FoxM1 in CRC cells and that the inhibition of FoxM1 impeded Gli1-mediated CRC cell proliferation. FoxM1 expression was also recently reported to be modulated by many other transcription factors, and Her2 reportedly upregulated FoxM1 expression in gastric cancer [ 51 ]. FoxM1 was also shown to be transactivated by HSF1, which promoted the survival of glioma cells under heat shock stress [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the association between HER-2 gene amplification and disease prognosis was demonstrated (10,11), overexpression of the gene has been observed in a variety of primary human carcinoma, including breast cancer (12,13), gastric cancer (14,15), gastroesophageal adenocarcinomas (16) and mucinous epithelial ovarian cancer (17). Initially, HER-2 was found to be upregulated in meningioma (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…The FOXM1 regulon also showed great overlap with Kang doxorubicin resistance gene set. Recently, Qi W. et al demonstrated that the regulation of the level of ERBB2 in the gastric cancer cell lines, accordingly produced a change in the expression of FOXM1, indicating that the expression level of FOXM1 was at least partially regulated by ERBB2 [56]. Interestingly, Qi W. et al also revealed that FOXM1 and ERBB2 expression was associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%